Tripartite Motif Protein 6 Promotes Colorectal Cancer Cell Migration and Metastasis via SOCS2-STAT3 Signaling - Zhao, Hongjian; Huang, Junjun; Chen, Ming; Li, Baoru; Chen, Xinran; Zhou, Mingqing (Frontiers in Oncology, 2021)
Colorectal cancer (CRC) is one of the leading causes of cancerous death worldwide. Majority of CRC related mortality is caused by CRC metastases. The underlying molecular mechanism of CRC metastases remains largely unknown. Emerging evidences have shown the role of TRIM family, especially TRIM6, in carcinogenesis. In this study, we used TRIM6 knockdown and overexpression CRC cell lines to investigate TRIM6 function in CRC metastasis. Our results indicate that TRIM6 promotes CRC cell migration and invasion both in vitro and in vivo. TRIM6 knockdown slows down the migration and invasion processes, whereas TRIM6 overexpression accelerates CRC cell migration and invasion. TRIM6 is potentially the upstream regulatory factor for STAT3 via SOCS2. Samples from 70 patients further confirmed that TRIM6 expression level is positively correlated with phosphorylation of STAT3 while negatively correlated with SOCS2 expression. Our results reveal that TRIM6 could be a potential therapeutic target for CRC metastasis.